Noninvasive Imaging of Early Venous Thrombosis by 19F Magnetic Resonance Imaging With Targeted Perfluorocarbon Nanoemulsions. Issue 16 (21st April 2015) - Temme, Sebastian; Grapentin, Christoph; Quast, Christine; Jacoby, Christoph; Grandoch, Maria; Ding, Zhaoping; Owenier, Christoph; Mayenfels, Friederike; Fischer, Jens W.; Schubert, Rolf; Schrader, Jürgen; Flögel, Ulrich
<x xml:space="preserve">Abstract</x> Background— Noninvasive detection of deep venous thrombi and subsequent pulmonary thromboembolism is a serious medical challenge, since both incidences are difficult to identify by conventional ultrasound techniques. Methods and Results— Here, we report a novel technique for the sensitive and specific identification of developing thrombi using background-free 19F magnetic resonance imaging, together with α2-antiplasmin peptide (α2AP)–targeted perfluorocarbon nanoemulsions (PFCs) as contrast agent, which is cross-linked to fibrin by active factor XIII. Ligand functionality was ensured by mild coupling conditions using the sterol-based postinsertion technique. Developing thrombi with a diameter <0.8 mm could be visualized unequivocally in the murine inferior vena cava as hot spots in vivo by simultaneous acquisition of anatomic matching 1H and 19F magnetic resonance images at 9.4 T with both excellent signal-to-noise and contrast-to-noise ratios (71±22 and 17±5, respectively). Furthermore, α2AP-PFCs could be successfully applied for the diagnosis of experimentally induced pulmonary thromboembolism. In line with the reported half-life of factor XIIIa, application of α2AP-PFCs >60 minutes after thrombus induction no longer resulted in detectable 19F magnetic resonance imaging signals. Corresponding results were obtained in ex vivo generated human clots. Thus, α2AP-PFCs can visualize freshly developed thrombi that might still be susceptible to pharmacological intervention. Conclusions— Our results demonstrate that 1H/19F magnetic resonance imaging, together with α2AP-PFCs, is a sensitive, noninvasive technique for the diagnosis of acute deep venous thrombi and pulmonary thromboemboli. Furthermore, ligand coupling by the sterol-based postinsertion technique represents a unique platform for the specific targeting of PFCs for in vivo 19F magnetic resonance imaging.